2002
DOI: 10.1590/s0004-282x2002000100026
|View full text |Cite
|
Sign up to set email alerts
|

Instrumentação anterior da coluna em espondilite tuberculosa mal de pott: Relato de caso

Abstract: RESUMO -Relatamos caso de tratamento cirúrgico com instrumentação anterior em espondilite tuberculosa (mal de Pott), em mulher de 71 anos, que se encontrava em tratamento para tuberculose na forma pulmonar e evoluiu com dor lombar, dificuldade progressiva para deambular, cifose e disfunção vesical. A ressonância magnética revelou lesão nos corpos vertebrais de T12 e L1 com abcesso paravertebral. A paciente foi tratada cirurgicamente por acesso tóraco-abdominal lateral. Os corpos vertebrais foram ressecados, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Unlike cervical spine fusion, which requires less autologous bone, anterior lumbar reconstruction not only requires more autologous bone, but also requires bicortical or tripcortical bone to provide support. In 2002, Farage et al first reported the use of titanium mesh for intervertebral bone graft support to reconstruct the anterior spinal column for the treatment of spinal tuberculosis ( 25 ). The titanium mesh has a simple structure and has a good biocompatibility and strong support strength.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike cervical spine fusion, which requires less autologous bone, anterior lumbar reconstruction not only requires more autologous bone, but also requires bicortical or tripcortical bone to provide support. In 2002, Farage et al first reported the use of titanium mesh for intervertebral bone graft support to reconstruct the anterior spinal column for the treatment of spinal tuberculosis ( 25 ). The titanium mesh has a simple structure and has a good biocompatibility and strong support strength.…”
Section: Discussionmentioning
confidence: 99%